Teaching pronunciation throungh experiential learning and pronunciation techniques. - Martínez Castellanos, Cristian Andrés (Corporación Universitaria Minuto de Dios, 2016)
During the observation of four English classes at the beginning of a professional practicum in the second half of 2015 in a private school in Bogota, it was observed students had some pronunciation problems when they spoke and performed short conversations in listening and speaking activities. It looks like a simple problem; but the reality is that it is an aspect which may cause negative implications in students’ learning process because pronunciation is an aspect that is linked with speaking and listening mainly (Bearte K., 2O14). If you analyze this point of view you might say: What is the relationship among them? The answer is simple. Whether you pronounce a word or sets of words wrongly, at the beginning, you do not notice the consequences. Those consequences are related to there is a great quantity of words with minimal pairs which have completely different meanings to each other. An example of this is: ‘she went to bet VS she went to bed (bet VS bed)’. However, when you progress, you realize whether you are able to pronounce a word correctly, you can listen and understand it without any problem. But if you pronounce something wrongly, you might probably generate misunderstandings and that is why this project took for topic EFL pronunciation.
Keywords: Pronunciation Problems; Learning Process; Speaking and Listening; Ingles-Enseñanza; Aprendizaje Verbal; Aprendizaje; Aptitud de Aprendizaje